Function call interception techniques - Kang, Pilsung (Software, practice & experience, 2018)
Summary Function call interception (FCI), or method call interception (MCI) in the object‐oriented programming domain, is a technique of intercepting function calls at program runtime. Without directly modifying the original code, FCI enables to undertake certain operations before and/or after the called function or even to replace the intercepted call. Thanks to this capability, FCI has been typically used to profile programs, where functions of interest are dynamically intercepted by instrumentation code so that the execution control is transferred to an external module that performs execution time measurement or logging operations. In addition, FCI allows for manipulating the runtime behavior of program components at the fine‐grained function level, which can be useful in changing an application's original behavior at runtime to meet certain execution requirements such as maintaining performance characteristics for different input problem sets. Due to this capability, however, some FCI techniques can be used as a basis of many security exploits for vulnerable systems. In this paper, we survey a variety of FCI techniques and tools along with their applications to diverse areas in the computing and software domains. We describe static and dynamic FCI techniques at large and discuss the strengths and weaknesses of different implementations in this category. In addition, we also discuss aspect‐oriented programming implementation techniques for intercepting method calls.